2008
DOI: 10.1021/cm702610h
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Mesoporous Silica to Study the Preparation of Ni/SiO2 ex Nitrate Catalysts: Impregnation, Drying, and Thermal Treatments

Abstract: In this contribution, we investigated the preparation of Ni/SiO 2 catalysts with aqueous [Ni(OH 2 ) 6 ](NO 3 ) 2 solutions via the impregnation and drying method using ordered mesoporous silica SBA-15 (mesopore diameter of 9 nm) as model support to study each step in the preparation: impregnation, drying, calcination, and reduction. After impregnation, not all the mesopores of SBA-15 appeared filled with precursor solution. Consecutive drying led to formation of 9 nm Ni 3 (NO 3 ) 2 (OH) 4 crystallites exclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
151
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(164 citation statements)
references
References 54 publications
8
151
0
Order By: Relevance
“…A non-uniform distribution of NiO over the mesopores was found in all three samples. The presence of unfilled pores with ordered mesoporous silica supported metal (oxide) catalysts has been observed by others too [46,47] and is presumably related to non-uniform wetting during impregnation [48]. The NiO/SBA-15 sample obtained through air calcination contained both large NiO particles outside the mesopores and particles retained inside the pores.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…A non-uniform distribution of NiO over the mesopores was found in all three samples. The presence of unfilled pores with ordered mesoporous silica supported metal (oxide) catalysts has been observed by others too [46,47] and is presumably related to non-uniform wetting during impregnation [48]. The NiO/SBA-15 sample obtained through air calcination contained both large NiO particles outside the mesopores and particles retained inside the pores.…”
Section: Resultsmentioning
confidence: 56%
“…7). It has already [48,61]. Moreover, we recently discovered that N 2 O also has an advantageous effect [62].…”
Section: Resultsmentioning
confidence: 99%
“…2,23À25 A number of methods to counter agglomeration of transition metal nitrates such as nickel, cobalt, and copper nitrate have been reported, including replacement of the air calcination by glow discharge plasma-assisted nitrate decomposition 26 and direct reduction of the metal nitrate to the metal, omitting air thermal treatment. 5,25,27,28 Another approach is fast removal of the decomposition gases via high space velocities or evacuation. 24, 29 We have previously reported that agglomeration of cobalt and nickel nitrate can effectively be prevented by replacing traditional air calcination with thermal treatment in 1% (v/v) NO/He flow, resulting in high NiO and Co 3 O 4 dispersions.…”
Section: ' Introductionmentioning
confidence: 99%
“…Thus, metal nitrates have indeed been used as precursors for the generation of metal oxides and due to the oxidizing properties of nitrates also high oxidation states may be maintained in the products resulting from thermolysis. [1,2] Recently, controlled pyrolysis of metal nitrates has also been proposed as a new route for the preparation of metal oxide nanoparticles, [3,4] and NiO/ SiO 2 catalysts with narrow distributions of particle sizes and particle-particle distances have also been obtained. [5,6] The mechanistic knowledge about the details of the thermal decomposition of nitrates is limited, however, mostly due to the complex radical chain mechanisms that are involved ions containing formal M III .…”
Section: Introductionmentioning
confidence: 99%